Annual Plan 2001-02 Volume I Planning, Statistics and Science and Technology Department - Planning Commission (Planning Commission, 2001)
The budgeted outlay for the Annual Plan 2001-02 is Rs. 8588.28 crores. The budgeted outlay represents an increase of 27 per cent over the revised outlay of 2000-01 and 18 per cent over the budgeted outlay. The district Plan for 2001-02 has been fixed al Rs. 1083.21 crores. This represents an increase of 12.6% over the district plan outlay for 2000-01. The outlay for externally aided projects in 2001-02 is Rs. 1048.93 crores. Under the Special Component Plan Rs. 606.58 crores have been earmarked for the Welfare of Scheduled Castes and Rs. 134.10 crorcs for the Scheduled Tribes under the Tribal Sub Plan."
Planning, Statistics and Science and Technology Department
Planning, Statistics and Science and Technology Department